PENILAIAN POTENSI DAYA TARIK BUKIT JAMUR DI DESA BHAKTI MULYA KABUPATEN BENGKAYANG - Injoi, .; Kartikawati, Siti Masitoh; Siahaan, Sarma (JURNAL HUTAN LESTARI, 2019)
Bengkayang Regency is one of the regencies in West Borneo Province which has a diversity of resources and natural magnificence, that is Bukit Jamur, nature tourism is one of the activities that utilize the potential of natural resources and environmental management. This study aims to assess the potential of the Bukit Jamur natural tourism magnetism in Belangko, Bhakti Mulya Village, in Bengkayang Regency. The method used in this research is accidental sampling through interview techniques and the tool used for the data collection is questionnaire. The calculation results of the assessment criteria based on the 2003 ODKA ODTWA development standard classification that is the assessment of tourist magnetism, with the score 1004 or (B). This shows the magnetism of Bukit Jamur is potentially being developed as a natural tourist magnetism in Belangko, Bhakti Mulya Village, in Bengkayang Regency.Keywords: Assessment, Bengkayang, Bukit Jamur, ODTWA.